Advanced Energy Systems 2002
DOI: 10.1115/imece2002-33078
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Low Heat Rejection Diesel Engine With Crude Jatropha Oil as an Alternate Fuel

Abstract: Jatropha oil, a non-edible vegetable oil shows a greater potential for replacing conventional diesel fuel quite effectively, as its properties are compatible to that of diesel fuel. But low volatility and high viscosity of jatropha oil call for hot combustion chamber, which is provided by a low heat rejection diesel engine with threaded air gap piston and liner with superni-90 inserts. The performance of the engine with jatropha oil is obtained with different versions of the engine such as conventional engine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…There was a 6% reduction in VE for used cooking oil operation in comparison to diesel fuel operation, the reason being the accumulation of more quantity of unburnt fuel. Earlier studies also revealed the same trends [13,17] The values of Volumetric efficiency were observed to be in ascending order for used cooking oil, biodiesel and diesel. This Was because of better combustion in case of diesel…”
Section: Figure 5: the Variation Of Exhaust Gas Temperature (Egt) Witsupporting
confidence: 67%
“…There was a 6% reduction in VE for used cooking oil operation in comparison to diesel fuel operation, the reason being the accumulation of more quantity of unburnt fuel. Earlier studies also revealed the same trends [13,17] The values of Volumetric efficiency were observed to be in ascending order for used cooking oil, biodiesel and diesel. This Was because of better combustion in case of diesel…”
Section: Figure 5: the Variation Of Exhaust Gas Temperature (Egt) Witsupporting
confidence: 67%
“…free fatty acids [31].The methyl ester was produced by chemically reacting the linseed oil with an alcohol (methyl), in the presence of a catalyst (KOH). A two-stage process was used for the esterification [32][33] of the waste fried vegetable oil. The first stage (acid-catalyzed) of the process is to reduce the free fatty acids (FFA) content in linseed oil by esterification with methanol (99% pure) and acid catalyst (sulfuric acid-98% pure) in one hour time of reaction at 55°C.…”
Section: Methodsmentioning
confidence: 99%
“…Air gap was created (Rama Mohan et al, 1999) in the nimonic piston crown and experiments were conducted with pure diesel and reported that BSFC increased by 7% with varied injection timings. Investigations were carried (Murali Krishna, 2004) with air gap insulated piston with superni crown and air gap insulated liner with superni insert with varied injection pressures and injection timings with alternate fuels of alcohols and vegetable oils and reported LHR engine improved efficiency and decreased pollution levels.…”
Section: Introductionmentioning
confidence: 99%